Implementation of E-Voting in the Village Head Election (Pilkades) Selotinatah, Ngariboyo District, Magetan Regency - Desi Rachawati; Asep Nurjaman; Iradhad Taqwa Sihidi (Universitas Teuku Umar, 2022)
E-Voting is an innovation in the village-level electoral (Pilkades) process carried out simultaneously in Magetan Regency for the first time in 2019. The purpose of this study was to describe the implementation of E-Voting elections using the theory of Merilee S. Grindle and taking the locus in Selotinatah Village, Ngariboyo District, with rationalization as the village with the largest population and the most significant area. This research method uses descriptive qualitative research with primary and secondary sources. The results of this study indicate that the implementation of E-Voting in Selotinah Village has been going well. It can be seen from the process that it is concluded that it is efficient and effective in accommodating the political participation of villagers. However, as a new process, socialization and technology quality constraints are again a problem. This is a classic problem in the implementation of public policies in Indonesia, so improvements are needed, especially in the bureaucracy's capacity and the security of the technology adopted.